A network meta-analysis of efficacy and safety for first-line and maintenance therapies in patients with unresectable colorectal liver metastases - Jiang, Yunlin; Shao, Taihang; Zhao, Mingye; Xue, Yahong; Zheng, Xueping (Frontiers in Pharmacology, 2024)
Background Evidence comparing the efficacy of different treatments for patients with unresectable colorectal liver metastases (CRLM) receiving first-line or maintenance therapy is sparse. We aimed to assess the efficacy and safety of these treatments, with a distinct focus on evaluating first-line and maintenance treatments separately.We conducted Bayesian network meta-analyses, sourcing English-language randomized controlled trials (RCTs) published through July 2023 from databases including PubMed, Embase, the Cochrane Library, ClinicalTrials.gov, and key conference proceedings. Phase Ⅱ or Ⅲ trials that assessed two or more therapeutic regimens were included. Primary outcome was overall survival (OS).Secondary outcomes included progression-free survival (PFS), objective response rate (ORR), adverse events graded as 3 or above (SAE), and R0 liver resection rate. Hazards Ratios (HRs) and 95% confidence intervals (CI) were used as effect size for OS and PFS, Odds Ratios (ORs) and 95% CI were used for ORR, SAEs and R0 resection rate. Subgroup and sensitive analyses were conducted to analysis the model uncertainty (PROSPERO: CRD42023420498). Results 56 RCTs were included (50 for first-line treatment, six for maintenance therapies), with a total of 21,323 patients. Regarding first-line, for OS, the top three mechanisms were: local treatment+singledrug chemotherapy (SingleCT), Targeted therapy (TAR)+SingleCT, and TAR+multi-drug chemotherapy (MultiCT). Resection or ablation (R/A)+SingleCT, S1, and Cetuximab+intensified fluorouracil-based combination chemotherapy (ICTFU) were identified as the best treatments. For PFS, the top three mechanisms were: Immune therapy+TAR+MultiCT, multi-targeted therapy (MultiTAR), TAR+SingleCT. The top three treatments were: Atezolizumab+Bevacizumab+fluorouracil-based combination chemotherapy (CTFU), TAS-102+bevacizumab, Bevacizumab+ICTFU.Cetuximab+CTFU was the best choice for RAS/RAF wild-type patients. Regarding maintenance treatment, Bevacizumab+SingleCT and Adavosertib were the best options for OS and PFS, respectively.For safety, MultiCT was the safest, followed by local treatment+MultiCT, TAR+MultiCT caused the most SAEs. Bevacizumab plus chemotherapy was found to be the safest among all targeted combination therapies. Conclusions In first-line, local treatment or targeted therapsy plus chemotherapy are the best mechanisms. R/A+SingleCT or CTFU performed the best for OS, Atezolizumab+Bevacizumab+ICTFU was the best option regarding PFS. For RAS/RAF wild-type patients, Cetuximab+CTFU was the optimal option. Monotherapy may be preferred choice for maintenance treatment. Combination therapy resulted in more SAEs when compared to standard chemotherapy.